Outpatient Care Utilization among Elderly in South Sumatra Based on National Social-Economic Survey Data - Misnaniarti, Misnaniarti; Etrawati, Fenny (Media Kesehatan Masyarakat Indonesia, 2020)
Implementation of National Health Insurance is thought to be the cause of increasing number of visits to health facilities, especially in elderly people who tend to be in sick. This study aims to analyze the outpatient utilization by elderly in South Sumatera region. Study design was cross-sectional. Samples was elderly in South Sumatra (n = 2,833 people). Study done on 2016, using data from Survei Sosial Ekonomi Nasional (Susenas) at 2015. Data analysis used chi-square test and multiple logistic regression. Based on the study known that outpatient utilization of elderly in all health facilities during the past month amounted to 29.2%. Providers selected when elderly needed of outpatient treatment, most often visited to the doctor's practice/midwife's practice (46.2%), and puskesmas (24.2%). Elderly who has private health insurance have a tendency was 1.9 times greater (OR=1.9) to utilize outpatient compared to elderly who do not have insurance. Its concluded that variables associated with outpatient care utilization are: health insurance membership (OR=1.9) and work activity (OR=1.5). It is recommended for elderly to remain active in their activities so that they can realize the healthy and active aging and reduce the sick visits to health facilities.